2009
DOI: 10.1080/13683500903042881
|View full text |Cite
|
Sign up to set email alerts
|

More than the kill: hunters' relationships with landscape and prey

Abstract: Through a discussion of the perceptions of hunters within a New Zealand tourism context, this paper explores how different perspectives of the 'connection' between hunter and prey are performed by participants and analysed by scholars using distinct ethical approaches. It attempts to contribute to the conversation about hunting ethics within the tourism and recreation fields by discussing the limitations of environmental ethical positions involved in analysing hunters' narratives and performances while engagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 23 publications
(12 reference statements)
1
14
0
Order By: Relevance
“…In the aforementioned study by Daigle et al (), all 3 groups studied (hunters, wildlife watchers, and other outdoor recreationist) placed a very high value on wildlife enjoyment. Additional research has shown that both hunters and birdwatchers are primarily motivated by being close to nature (Decker et al , McFarlane , Adams et al , Reis ), and both hunters and birdwatchers are invested in preserving wildlife habitat and ecosystems that support their favorite recreation activities (U.S. Fish and Wildlife Service ).…”
mentioning
confidence: 99%
“…In the aforementioned study by Daigle et al (), all 3 groups studied (hunters, wildlife watchers, and other outdoor recreationist) placed a very high value on wildlife enjoyment. Additional research has shown that both hunters and birdwatchers are primarily motivated by being close to nature (Decker et al , McFarlane , Adams et al , Reis ), and both hunters and birdwatchers are invested in preserving wildlife habitat and ecosystems that support their favorite recreation activities (U.S. Fish and Wildlife Service ).…”
mentioning
confidence: 99%
“…Lastly, as a researcher of hunters' experiences, but not a hunter myself, I was regularly exposed, willingly, to hunters, and therefore was constantly questioning and being questioned about my understandings of this practice. In this regard, a significant occurrence comes to mind that happened as I presented some initial thoughts about my research material in an interdisciplinary conference in Dunedin, New Zealand (Carvalhedo Reis, 2009). As I was discussing what I perceived to be hunters' contradictory treatment of different species of animals, an argument that I sustain but now with a slightly different take, I was somewhat aggressively questioned by an academic in the audience who was himself a hunter and who felt extremely upset by my comments/'findings'.…”
Section: A Reflexive and Embedded Methodologymentioning
confidence: 95%
“…Also, I hoped to make clearer my own position through the use of a different form of language, that is, visual and affective language. These photographs were used in the chapter of my thesis that presented discussions about New Zealand hunters' engagement with the natural environment, particularly the power of the sublime landscape of Stewart Island on hunters' embodied experiences and narratives (see also Reis, 2009). Being an extremely rugged location, isolated in many ways from urban contemporary life and representing a typical New Zealand sublime nature, the pictures enmeshed with the text were my means of 'translating', however possible this may be, how one may view, feel and experience such an environment.…”
Section: Bringing My Creative Self To the Forementioning
confidence: 99%
“…But most importantly, it is because of the fact that all of these contrasting constructions of Nature are available at any one time in society that discourses and performances can be so inconsistent, since they can easily fluctuate between the diverse ways of understanding Nature. In this sense, it seems very unlikely that most of the visitors engaging with nature-based tourism experiences will have developed consistent and coherent positions in regards to the natural environment and to the nonhuman animals who take part in their experiences in the outdoors [Bishop (2004) Peace (2001), and Reis (2009) present interesting discussions in this regard]. Moreover, tourists' ways of articulating their positions through narrative and performance also will likely be inconsistent.…”
Section: Nearby Naturementioning
confidence: 91%